I think is yes but I’m not sure
Answer:
(-2, 4)
Step-by-step explanation:
Hopes this helps!
40 or 45 degrees I say dis cuz if u find da overall area then u can find the degrees
Answer: 2√2 - 3Explanation:The expession written properly is:
![\frac{ \sqrt{3}- \sqrt{6} }{ \sqrt{3}+ \sqrt{6} }](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%5Csqrt%7B3%7D-%20%5Csqrt%7B6%7D%20%20%7D%7B%20%5Csqrt%7B3%7D%2B%20%5Csqrt%7B6%7D%20%7D%20)
To rationalize that kind of expressions, this is to eliminate the radicals on the denominator you use conjugate rationalization.
That is, you have to multiply both numerator and denominator times the conjugate of the denominator.
The conjugate of √3+√6 is √3 - √6, so let's do it:
![\frac{ \sqrt{3} - \sqrt{6} }{ \sqrt{3} + \sqrt{6} } . \frac{ \sqrt{3}- \sqrt{6} }{ \sqrt{3}- \sqrt{6} }](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%5Csqrt%7B3%7D%20-%20%5Csqrt%7B6%7D%20%7D%7B%20%5Csqrt%7B3%7D%20%2B%20%5Csqrt%7B6%7D%20%7D%20.%20%5Cfrac%7B%20%5Csqrt%7B3%7D-%20%5Csqrt%7B6%7D%20%20%7D%7B%20%5Csqrt%7B3%7D-%20%5Csqrt%7B6%7D%20%7D%20)
To help you with the solution of that expression, I will show each part.
1) Numerator: (√3 - √6) . (√3 - √6) = (√3 - √6)^2 = (√3)^2 - 2√3√6 + (√6)^2 =
= 3 - 2√18 + 6 = 9 - 6√2.
2) Denominator: (√3 + √6).(√3 - √6) = (√3)^2 - (√6)^2 = 3 - 6 = - 3
3) Then the resulting expression is:
9 - 6√2
-----------
-3
Which can be further simplified, dividing by - 3
-3 + 2√2
Answer: 2√2 - 3
First you would have to find the base which would be 9^2 + 9^2= C^2 because of the pythagorean theorem. So the base would equal 12.7. To find the area of a triangle it’s A= h•b / 2. So your answer would be 95.25